Effect of Hypothermic Storage and Cryopreservation on Survival of Human Skin and Fibroblasts - Abrafikova, L. G.; Petrenko, T. F.; Vysekantsev, I. P. (Problems of Cryobiology and Cryomedicine, 2008)
It has been found that the bioptates of human skin after hypothermal storage for 14 days (observation term) preserve the ability of fibroblast formation. After cryopreservation with DMSO protection the bioptates lost this ability. In the experiments there was shown the possibility of fibroblast storage at 4ÂºC for 48 hrs.